2017
DOI: 10.1053/j.gastro.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sterile Fecal Filtrate Transfer for Treating Patients With Clostridium difficile Infection

Abstract: A preliminary investigation of 5 patients with CDI shows that transfer of sterile filtrates from donor stool (FFT), rather than fecal microbiota, can be sufficient to restore normal stool habits and eliminate symptoms. This finding indicates that bacterial components, metabolites, or bacteriophages mediate many of the effects of FMT, and that FFT might be an alternative approach, particularly for immunocompromised patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
448
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 550 publications
(489 citation statements)
references
References 51 publications
10
448
1
7
Order By: Relevance
“…Given the timescale of these microbial changes, it seems unfeasible that the apparent improvement in PHES testing/ EncephalApp-Stroop and reduced HE events (all outcomes measured at day 15 post-FMT or later) was attributable to Lachnospiraceae and Ruminococcaceae members derived from the FMT. Recent data demonstrate that sterile stool filtrates may have similar efficacy in treating recurrent Clostridium difficile infection as conventional FMT 5 , consistent with bacterially-derived proteins, gut metabolites, bacteriophages or other filtrate o po e ts ei g the ediators of FMT's effi a y i treati g this o ditio , as opposed to intact microorganisms. By extrapolation, for future studies in this area, a more rational means of donor selection may be based around not purely matching the structure of the gut microbiota, but to select donors with the gut microbiota functionality missing in HE.…”
mentioning
confidence: 83%
“…Given the timescale of these microbial changes, it seems unfeasible that the apparent improvement in PHES testing/ EncephalApp-Stroop and reduced HE events (all outcomes measured at day 15 post-FMT or later) was attributable to Lachnospiraceae and Ruminococcaceae members derived from the FMT. Recent data demonstrate that sterile stool filtrates may have similar efficacy in treating recurrent Clostridium difficile infection as conventional FMT 5 , consistent with bacterially-derived proteins, gut metabolites, bacteriophages or other filtrate o po e ts ei g the ediators of FMT's effi a y i treati g this o ditio , as opposed to intact microorganisms. By extrapolation, for future studies in this area, a more rational means of donor selection may be based around not purely matching the structure of the gut microbiota, but to select donors with the gut microbiota functionality missing in HE.…”
mentioning
confidence: 83%
“…Previous research has demonstrated that commensal bacteria cultured from the stool of healthy donors,22 sterile faecal filtrate23 and/or spores of Firmicutes derived from ethanol-treated stool from healthy donors24 may have similar efficacy to conventional FMT in treating CDI, although results of the latter approach produced disappointing outcome data when extended to a phase II clinical trial 25. For the purposes of this guideline, the BSG/HIS working group considered only studies that used the administration of manipulated whole stool (including encapsulated faeces).…”
Section: Introductionmentioning
confidence: 99%
“…Cependant, une publication récente suggère qu'un filtrat fécal ne contenant pas de bactérie était suffisant pour guérir des patients infectésp ar Clostridium difficile [8]. Selon les auteurs, les ingrédients actifs pourraient être en fait des métabolites bactériens, ou même des bactériophages.…”
Section: Resultsunclassified